FORMULATION AND EVALUATION OF HERBAL ANTIBACTERIAL GEL CONTAINING ETHANOLIC EXTRACT OF MIKANIA MICRANTHA KUNTH LEAVES - Harahap, Nina Irmayanti; Nainggolan, Marline; Harahap, Urip (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study was to check the effectiveness of Mikania micrantha Kunth against the microbial species of Staphylococcus epidermis, to observe the zone of inhibition, and to develop a topical gel formulation of M. micrantha Kunth for the treatment of acne vulgaris. Methods: The extraction was done by maceration method and continues with phytochemical screening and herbal gel formulation (four formulas) using hydroxylpropyl methylcellulose as a base. The gel was evaluated for the physical appearance, pH, homogeneity, and antibacterial. Result: The ethanolic extract of M. micrantha Kunth had a high value of alkaloids, flavonoids, and tannins. All of the formula (F1-F4) showed a good result in physicochemical and antibacterial evaluation. Conclusion: M. micrantha Kunth can be used to treat the skin diseases, especially acne vulgaris problem.